Black-Scholes Model and Binomial Model Tests on Nvidia Stock Option Contracts - Dewi, Andrieta Shintia; Sari, Maya; Sastika, Widya; Afifah, Nurul; Pawitra, Mohammad Tyas; Wibowo, Lili Adi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
In order to invest, investors can purchase a number of shares. The characteristics of stocks are high risk/high return and low risk/low return. Stock price volatility is a measurement of how quickly and in a short period of time stock prices can rise or fall (fluctuate). With the advent of derivative instruments, specifically options, risk can be reduced in several ways. A contract known as an option grants its owner the right, but not the duty, to sell or acquire a specific quantity of the underlying asset at a specified price at a specific point in the future. Methods for calculating option prices in derivative instruments is the Binomial option model and the Black Scholes option model. The aim of this research to determine the accuracy of the Black Scholes compared with the Binomial in predicting call option shares of Nvidia Coorporation (NVDA) on the due date of 1 month, 2 months, and 3 months, using data price daily and call option which at 17 sample from January 2022 to May 2023. To determine the accuracy use price absolute error comparisson between the Black Scholes and the Binomial was conducted. In result the Black Scholes model is more accurate than the Binomial.